Fully simplify using only positive exponents. \[ \frac{2 x^{7} y^{3}}{x^{6} y^{5}} \]
Solución de tutoría real
Responder
Solución
Revisado y aprobado por el equipo de tutoría de UpStudy
Beyond the Answer
To simplify the expression \(\frac{2 x^{7} y^{3}}{x^{6} y^{5}}\), we begin by dividing the coefficients and then the powers of the variables separately. 1. Dividing the coefficients: \[ \frac{2}{1} = 2 \] 2. Dividing the powers of \(x\): \[ x^{7} \div x^{6} = x^{7-6} = x^{1} = x \] 3. Dividing the powers of \(y\): \[ y^{3} \div y^{5} = y^{3-5} = y^{-2} \] Since we only want positive exponents, we rewrite \(y^{-2}\) as \(\frac{1}{y^{2}}\). Now putting it all together: \[ \frac{2 x^{1} y^{3}}{x^{6} y^{5}} = 2 x \cdot \frac{1}{y^{2}} = \frac{2x}{y^{2}} \] Thus, the fully simplified expression is: \[ \frac{2x}{y^{2}} \]